Hubungan Antara Penerapan Strategi Pembelajaran Dengan Aktivitas Belajar Siswa sma Negeri 1 Metro - Hanwar Priyo Handoko (Jurnal Dewantara, 2018)
The problem in this study is the application of learning strategies carried out by teachers in SMA N 1 Metro is good, but student learning activities are still classified as lacking. The formulation of the problem that the authors propose is: Is there a significant relationship between the applications of learning strategies to student learning activities. While the purpose of this study is to determine the level of closeness of the relationship between the application of learning strategies to student learning activities. To obtain the data of the author using the questionnaire, observation, documentation, and intervieu methods. Furthermore, using the data analysis method with the Product Moment formula can be obtained rXY results of 0.330 greater than the r table, both at the significance level of 1% and the significance level of 5%, which then obtained results for a 1% significance level of 0.325 and for the significance level 5 % of 0,250. The hypothesis that the authors propose is accepted, meaning there is a weak relationship between the applications of learning strategies to student learning activities.